The philosophy of neo-noir - Conard, Mark T., 1965- (Lexington, Ky. : University Press of Kentucky, 2007)
Film noir--a cycle of American films from the 1940s and '50s--is characterized not only by a constant opposition of light and shadow and a disruptive compositional balance of frames and scenes, but also by dark, foreboding characters and plots and an overriding sense of alienation and moral ambiguity. Noir films reflect the sense of loss, fragmentation, and nihilism at the heart of the human condition in the twentieth century. Although the classic film noir period ended in the late 1950s, its impact on more films has been profound. While typically not black and white, these new films incorpor.
pt. 1. Subjectivity, knowledge, and human nature in neo-noir -- pt. 2. Justice, guilt, and redemption : morality in neo-noir -- pt. 3. Elements of neo-noir.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Film noir -- United States -- History and criticism; Films noirs -- États-Unis -- Histoire et critique; PERFORMING ARTS -- Film & Video -- Reference; PHILOSOPHY -- General; Film noir; United States; Film noir; Philosophie; USA; dissertations; Criticism, interpretation, etc; Academic theses; Thèses et écrits académiques.; Electronic books; Aufsatzsammlung